Menguji Resistansi Doktrin Khilafah Hizbut Tahrir Indonesia (HTI); Sebuah Kajian Analitis dan Historiografis - Arif, Muhammad Syamsul (FIKRAH, 2019)
Hizbut Tahrir Indonesia (HTI) is one of the most active Islamic movements in Indonesia's contemporary history that seeks to implement Islam in a serious way. For political ideology and political thought, this party has no fundamental difference with central Hizbut Tahrir, and puts the idea of realizing the global caliphate at the center of its thinking. Is the global caliphate suitable idea for contemporary heterogeneous Indonesian society? Is historical, rational, hadith, and Quranic arguments obligate us to found global caliphate’s system such as HTI’s thinkers and activists have claimed? These are two fundamental issues that the present treatise seeks to answer. The treatise has demonstrated, with a descriptive, analytical, and critical method, that the global caliphate’s thought of Hizbut Tahrir Indonesia is in conflict with Islamic doctrines and historical defendable data.